South Australian four‐year‐old Aboriginal children: residence and socioeconomic status influence weight - Nicola J. Spurrier; Robert E. Volkmer; Christina Abi Abdallah; Alwin Chong (Australian and New Zealand Journal of Public Health, 2012)
Abstract Objective: Obesity rates have increased in children in Australia in the past 15 years. However, there is little available population data describing rates of overweight and obesity in Aboriginal children. Methods: Anthropometric data of four‐year‐old children (n=11,859) were collected by trained nurses at routine statewide preschool health checks during 2009. Weight status (underweight, healthy weight, overweight and obese) was determined using age and gender specific International Obesity Task Force (IOTF) cut‐points. Results: There were 337 Aboriginal children (3%) in the study population. Aboriginal children had significantly higher rates of overweight and obesity compared to non‐Aboriginal children (28% compared to 18% respectively, χ2p=0.0001). A statistically significant association between BMIz score and identifying as Aboriginal remained after controlling for rural/urban residence and socioeconomic status using multiple regression analyses. Conclusions: Aboriginal children have higher rates of overweight and obesity compared to their non‐Aboriginal peers by the time they are four years of age. Aboriginal children have higher BMIz scores compared to non‐Aboriginal children after controlling for rural/urban residence and socioeconomic status. Implications: A significant investment is required to optimise the health of Aboriginal women before pregnancy and throughout pregnancy. A rethink may be necessary in the approach to dietary management and catch‐up growth of Aboriginal children of low birth weight or having growth failure in early childhood.